The hydrolytic behavior of N, N′-(dimethylamino)ethyl acrylate-functionalized polymeric stars. Issue 34 (27th March 2017) - Rolph, Marianne S.; Pitto-Barry, Anaïs; O'Reilly, Rachel K.
Abstract : Well-defined N, N ′-(dimethylamino)ethyl acrylate (DMAEA) functionalized polymeric stars have been synthesized via an arm-first approach. Abstract : Well-defined N, N ′-(dimethylamino)ethyl acrylate (DMAEA) functionalized polymeric stars have been synthesized via an arm-first approach. Utilizing reversible addition–fragmentation chain transfer polymerization, linear homopolymers (PEGA, PHEA) were chain extended with DMAEA and a divinyl crosslinker to produce a series of crosslinked polymeric stars. These stars were characterized using a range of techniques including NMR, SEC, DLS and TEM analysis. The hydrolytic behavior of the DMAEA when tethered within a micellar core was investigated by 1 H NMR spectroscopy and was found to be strongly dependent on temperature. At elevated temperatures either a higher crosslinking density or a longer arm length was found to offer greater protection to the amine resulting in slower hydrolysis, with hydrolysis found to level off at a lower final percentage hydrolysis. In contrast, the composition and nature of the arm was found to have little impact on the hydrolysis, with the same trends relating to the effect of temperature and crosslinking density observed with a linear (HEA) and a brush (PEGA) arm. Additionally, the release of DMAE from the polymeric stars was successfully confirmed through the use of an enzymatic assay, producing a concentration of DMAE in good agreement with the theoretical concentration based on the 1 H NMR spectroscopic analysis.